2022
DOI: 10.7554/elife.71358
|View full text |Cite
|
Sign up to set email alerts
|

Circadian oscillations in Trichoderma atroviride and the role of core clock components in secondary metabolism, development, and mycoparasitism against the phytopathogen Botrytis cinerea

Abstract: Circadian clocks are important for an individual’s fitness, and recent studies have underlined their role in the outcome of biological interactions. However, the relevance of circadian clocks in fungal-fungal interactions remains largely unexplored. We sought to characterize a functional clock in the biocontrol agent Trichoderma atroviride to assess its importance in the mycoparasitic interaction against the phytopathogen Botrytis cinerea. By utilizing luciferase reporters to monitor the T. atroviride core-clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 108 publications
1
4
0
Order By: Relevance
“…Interestingly, 6-PP also belongs to this cluster. These data are in good agreement with the above-mentioned study, which investigated the effect of the circadian clock on secondary metabolite production including 6-PP in T. atroviride [71]. Higher production of 6-PP in PD has also been found in another recent study [42].…”
Section: Spatial Distribution Of Metabolites Produced Under Pd and Rlsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, 6-PP also belongs to this cluster. These data are in good agreement with the above-mentioned study, which investigated the effect of the circadian clock on secondary metabolite production including 6-PP in T. atroviride [71]. Higher production of 6-PP in PD has also been found in another recent study [42].…”
Section: Spatial Distribution Of Metabolites Produced Under Pd and Rlsupporting
confidence: 91%
“…A recent study investigated the effect of the circadian clock on the volatile and diffusible secondary metabolome of T. atroviride strain IMI 206040. A supposed secondary metabolite with a m / z value of 371.03 was reported, presumably fitting to a compound that we also found (MET463; putative molecular weight of neutral molecule 371.1829; number of carbon atoms 16, positive ionization mode) within the orange cluster [ 71 ].…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, according to our analysis, this is the least appropriate reference gene among those used in previous studies ( Supplementary Material 6 and 7 ). In the fungus N. crassa , this gene is under the control of its well-known circadian clock [ 85 ], a complex molecular machinery that in B. cinerea modulates time-dependent fungal–plant [ 86 ] and fungal–fungal dynamics [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, according to our analysis, it is the worst reference gene of those previously studied (Table 4 and Supplementary Material 4) . In the fungus Neurospora crassa , this gene is under the control of its well-known circadian clock (Shinohara et al, 1998), a complex molecular machinery that in B. cinerea modulates time-dependent fungal-plant (Hevia et al, 2015)) and fungal-fungal dynamics as recently demonstrated (Henríquez-Urrutia et al, 2022).…”
Section: Resultsmentioning
confidence: 99%